Effect of a Behavioral Self-Regulation Intervention on Patient Adherence to Fluid-Intake Restrictions in Hemodialysis: a Randomized Controlled Trial. Issue 2 (2nd December 2015) - Howren, M. Bryant; Kellerman, Quinn D.; Hillis, Stephen L.; Cvengros, Jamie; Lawton, William; Christensen, Alan J.
Abstract: Objective: The purpose of this study is to evaluate the efficacy of a behavioral self-regulation intervention vs. active control condition using a parallel-group randomized clinical trial with a sample of center hemodialysis patients with chronic kidney disease. Method: Participants were recruited from 8 hemodialysis treatment centers in the Midwest. Eligible patients were (a) fluid nonadherent as defined by an interdialytic weight gain >2.5 kg over a 4-week period, (b) >18 years of age, (c) English-speaking without severe cognitive impairment, (d) treated with center-based hemodialysis for >3 months, and (e) not living in a care facility in which meals were managed. Medical records were used to identify eligible patients. Patients were randomly assigned to either a behavioral self-regulation intervention or active control condition in which groups of 3–8 patients met for hour-long, weekly sessions for 7 weeks at their usual hemodialysis clinic. Primary analyses were intention-to-treat. Results: Sixty-one patients were randomized to the intervention while 58 were assigned to the attention-placebo support and discussion control. Covariate-adjusted between-subjects analyses demonstrated no unique intervention effect for the primary outcome, interdialytic weight gain ( β = 0.13, p = 0.48). Significant within-subjects improvement over time was observed for the intervention group ( β = −0.32, p = 0.014). Conclusions: The present study found that participation in a behavioral self-regulation intervention resulted in no unique intervention effect on a key indicator of adherence for those with severe chronic kidney disease. There was, however, modest within-subjects improvement in interdialytic weight gain for the intervention group which meshes with other evidence showing the utility of behavioral interventions in this patient population. ClinicalTrials.gov Identifier: NCT01066949